Partnership Strategy for Early Childhood Education Units In Increasing Parent Participation - Ujang Rahmat; Ahmad Hufad; Jajat Sudrajat Ardiwinata; Babang Robandi (Postgraduate, University of Mataram, 2023)
Parents are one of the important components that play a role in children's learning process in PAUD units. Examining PAUD unit partnership strategies to improve parental involvement is the aim of this research. The strategy used was descriptive qualitative research. The data used in this research was collected through observation, document collection, and interviews. After that, the information was reviewed using an interactive model validated by triangulation. The analysis, conclusions, and debates conducted on the results show that the partnership activities between Kober SPNF SKB Garut Regency and parents are based on standards that have been formalized in their implementation. Assistance and cooperation between families (parents) and PAUD units are the underlying principles of this relationship. The idea of 5C which stands for communication, connection, community, consultation, and cooperation is a reference in the partnership plan that has been implemented.